Seafood Pies with a Social Purpose - Johnson, Jeff (Maine Policy Review, 2011)
This case study profiles a value-added food production company that uses sustainably-harvested Maine seafood and locally-grown vegetables to make frozen seafood pies. Located in Maine’s poorest county, Washington, the Cobscook Bay Company donates 25 percent of its profits to a local education initiative.